EFFECT OF HYDRATION AND PACKING ORDER ON LARGE UNILAMELLAR VESICLE FUSION: THE ROLE OF CHOLESTEROL - Francisco J. Cuevas; Carolina A. Valle; Luis F. Aguilar (Journal of the Chilean Chemical Society, 2017)
Several studies examining vesicle fusion have been reported in last decades and have established a number of factors favoring the process of vesicle fusion. To determine whether variations to the physicochemical properties of the membrane affect the process of vesicle fusion, we worked with binary and ternary mixtures of large unilamellar vesicles (LUVs). The selected binary models were dioleoyl phosphocholine-cholesterol (DOPC-chol) and disteraroyl phosphocholine-cholesterol (DSPC-chol), and the tertiary mixtures were phosphatidylcholine-phsophatidylethanolamine-cholesterol (PC-PE-Chol); phosphatidylcholine-sphingomyelin-cholesterol (PC-SM-Chol); and phosphatidylcholine-phosphatidylserine-cholesterol (PC-PS-Chol). For all these models, the effect of cholesterol content on the lamella physicochemical properties was determined using 1,6-diphenyl-1,3,5-hexatriene (DPH) anisotropy, generalized polarization of 2-dimethylamino- 6-lauroylnaphthalene (Laurdan), and DPH fluorescence lifetime. To determine whether fusion of these vesicles varied according to lipid composition, the % mixing content and the % leakage were determined. Examining membrane incorporation using fluorescence steady-state and time-resolved probe assays in the models indicated that cholesterol content affected packing order and lamellar hydration. In most of the models, nonmonotonic variations were observed for these parameters, and these variations could be interpreted as increases in the proportion of ordered microdomains. When the proportion of these domains is higher, the packing order increases, and the lamellar water decrease. Similarly, the % mixing, which was assessed as a fusion parameter, also exhibited nonmonotonic behavior, indicating that the fusion process is enhanced at these concentrations of cholesterol. However, DSPC vesicles do not merge, so more than the presence of microdomains is required to stabilize fusion.